Revitalisasi Ijtihad: Upaya Meretas Kebekuan Pemikiran Islam dalam Menjawab Tantangan Zaman Modern - Sakti, Salwa Nurfauziyah; D, Dliyauddin; Hasan, Hamzah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Various attempts have been pioneered by modern Muslim scholars to revive the spirit of ijtihad. The revitalization of the Shariah maqasid, the renewal of ijtihad methodology, the strengthening of the fatwa institutions, as well as the reform of the Islamic education curriculum constitute strategic steps to restore ijtihad as the main axis of the renewal of Islamic law. Thus, this paper wants to study the problem of the freeze of ijtihad as well as decipher the efforts that need to be made so that ijtihad is able to absorb and respond to contemporary legal issues relevantly and solvetively. The freezing of ijtihad was the result of the accumulation of various factors: the politicization of religion, conservative education, the dominance of taqlid, to a stagnant religious culture. Whereas, Islam itself encourages ijtihad as a means of answering the challenges of the times. Therefore, the reactualization of ijtihad becomes an urgent need in building a contextualized and dynamic Islamic law. Efforts to break the freeze of ijtihad must be conducted comprehensively, covering aspects of methodology, education, institutions, and thought reform. Without ijtihad, Islamic law will lose its adaptability to the dynamics of the times. On the contrary, fresh and contextualized ijtihad is precisely evidence that Islamic sharia is capable of guiding mankind at all times.